1995
DOI: 10.1007/bf00016827
|View full text |Cite
|
Sign up to set email alerts
|

Demography and population growth of Asplanchna girodi (Rotifera) as a function of prey (Anuraeopsis fissa) density

Abstract: Laboratory studies on population growth and life table demography of Asplanchna girodi were conducted at 25±1 °c using Anuraeopsis fissa as prey at four (250, 500, 1000 and 2000 ind ml -1 ) densities . A prey density of 100 ind ml -1 per predator per day did not support A . girodi, while at the highest prey concentration, A . girodi reached a peak of 115±7 ind ml -1 . The age distribution of A. girodi indicated that non-adults constituted about 2/3rd of the population at all prey concentrations . A decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 23 publications
5
17
1
3
Order By: Relevance
“…The data of net reproductive rate of A. brightwelli obtained in the present study were much lower than those reported for Asplanchna (e.g., 9-15 offspring female x1 lifespan x1 for A. girodi; Dumont and Sarma, 1995), which might be attributed to the much lower prey biomass used here.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…The data of net reproductive rate of A. brightwelli obtained in the present study were much lower than those reported for Asplanchna (e.g., 9-15 offspring female x1 lifespan x1 for A. girodi; Dumont and Sarma, 1995), which might be attributed to the much lower prey biomass used here.…”
Section: Discussioncontrasting
confidence: 93%
“…The intrinsic rate of population increase of A. girodi obtained from life-table demography increased with increasing prey (B. havanaensis or B. calyciflorus) availability in the medium , but that of A. girodi was not significantly affected by A. fissa density (Dumont and Sarma, 1995). Similarly, in the present study, at 16 and 20 xC, B. angularis density did not affect the intrinsic rate of population increase of A. brightwelli.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations